A strategy of tailoring polymorphs and nanostructures to construct self-reinforced nonswelling high-strength bacterial cellulose hydrogels. Issue 32 (6th August 2019) - Zhang, Minghao; Chen, Shiyan; Sheng, Nan; Wang, Baoxiu; Yao, Jingjing; Wu, Zhuotong; Wang, Huaping
Abstract : High strength and non-swelling pure natural hydrogels with nanofiber-network-self-reinforced structures were fabricated through tailoring polymorphs and nanostructures. Abstract : A serious decline in mechanical properties of polysaccharide hydrogels caused by swelling has always been a difficult problem which greatly limited their application especially in the medical field. Herein, nonswelling high-strength natural hydrogels based on self-reinforced double-crosslinked bacterial cellulose (SDBC) were prepared. Inspired by the concept of homogeneous composite materials, by regulating the ratio of LiOH/urea alkaline solvent, the aggregation structure and nanostructure of SDBC hydrogels can be controlled, thereby a unique nanofiber-network-self-reinforced (FNSR) structure was constructed and a new self-reinforcing mechanism is proposed. The prepared SDBC hydrogels have excellent mechanical properties at a high water content (>91%) for the combination of double-crosslinking and a unique FNSR structure, which can effectively prevent crack propagation and dissipate a large amount of energy. In particular, the compressive strength can reach 3.17 MPa which is 56 times that of native bacterial cellulose (BC). It is worth mentioning that no swelling occurs for the hydrogel, and the mechanical strength still remains in excess of 90% for 15 days in water, which is favorable for promising application in underwater equipment, implantable ionic devices, and tissue engineering scaffolds. This study also opens up a new horizon for the preparation of self-reinforced hydrogels.